A low-cost alternative to the optical experiment commercially known as “Magic Hologram – 3D Mirage” - Silva, Osmar Henrique Moura (2014)
This work presents a low-cost alternative to the commercialized experiment called “Magic Hologram – Mirage 3D”, which reproduces the real image of an object that is seen three-dimensionally in the air. An analysis of this alternative is carried out, indicating educational aspects of its use in the classroom in quantitative terms.